2022
DOI: 10.1017/xps.2022.1
|View full text |Cite
|
Sign up to set email alerts
|

Can Appeals for Peace Promote Tolerance and Mitigate Support for Extremism? Evidence from an Experiment with Adolescents in Burkina Faso

Abstract: Recent efforts to improve attitudes toward outgroups and reduce support for extremists in violent settings report mixed results. Donors and aid organizations have spent millions of dollars to amplify the voices of moderate religious figures to counter violent extremism in West Africa, the Middle East, and South Asia. Despite this investment, we know little about whether such messaging persuades the primary recruits of violent extremist organizations: at-risk youth in fragile settings. In this paper, we conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…These findings share similarities with results from Kenya that endorsements from in-group members can persuade voters to support outgroup politicians (Arriola et al, 2022). They also complement burgeoning research on the role of trusted elites in shaping electoral or civic attitudes in developing democracies (McClendon & Riedl, 2019;Condra et al, 2019;Blair et al, 2021;A. Grossman et al, 2022).…”
supporting
confidence: 77%
See 1 more Smart Citation
“…These findings share similarities with results from Kenya that endorsements from in-group members can persuade voters to support outgroup politicians (Arriola et al, 2022). They also complement burgeoning research on the role of trusted elites in shaping electoral or civic attitudes in developing democracies (McClendon & Riedl, 2019;Condra et al, 2019;Blair et al, 2021;A. Grossman et al, 2022).…”
supporting
confidence: 77%
“…They also complement burgeoning research on the role of trusted elites in shaping electoral or civic attitudes in developing democracies (McClendon & Riedl, 2019; Condra et al, 2019; Blair et al, 2021; A. Grossman et al, 2022).…”
mentioning
confidence: 72%
“…The message of peacefulness from tolerance can be distributed to groups having diverse characteristics from the majority of people (Grossman, Nomikos, & Siddiqui, 2022). In the adolescent phase, the tolerance concepts are garnered as a result of the dialectic of tolerance in classroom learning or school environment.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence from Burkina Faso, for example, found that religious messaging failed to influence attitudes and behavior toward religious extremism. Worse, exposure to Islamic teachings actually reduced tolerance and inter-ethnic trust among participants from the dominant ethnic group (Grossman, Nomikos and Siddiqui, 2022).…”
Section: Theoretical Framework: Cve Message Content Effectsmentioning
confidence: 99%
“…Alternatively, VEO messages might undercut CVE campaigns by increasing grievances against governing authorities or stoking resentment against targeted groups (Grossman, Nomikos and Siddiqui, 2022), producing a null effect or even a pro-extremist attitudinal shift.…”
Section: The Effects Of Veo Counter-messagingmentioning
confidence: 99%